Pengolahan Sampah Anorganik sebagai Upaya Pengurangan Sisa Produksi pada Industri Pelumas - Brigitta Ardiana Diva Azzahra; Firra Rosariawari (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2025)
Increased production in the lubricant industry has become a significant issue because it generates production waste in the form of packaging, plastic, and paper waste as a direct consequence of manufacturing activities. Proper and systematic waste management is essential to reduce environmental impacts, comply with regulations, and support responsible and sustainable business practices. Lubricant production waste can damage the ecosystem and surrounding environment if not managed properly, so continuous innovation is needed to minimize environmental risks and reduce potential economic losses for the company. This study aims to analyze and implement effective waste management strategies using a combination of qualitative and quantitative approaches, including in-depth interviews with relevant stakeholders and analysis of secondary data obtained from company records. The waste management process begins with several waste reduction programs applied during the production stage to limit waste generation. Furthermore, the waste storage facility (TPS) available on the company’s premises, covering an area of 59 m², is capable of accommodating approximately 60% of the total waste that must be processed internally before further treatment or disposal.